Two years' test of a temperature sensing system based on fibre Bragg grating technology for the CMS GE1/1 detectors. (June 2020) - Abbas, M.; Abbrescia, M.; Abdalla, H.; Abu Zeid, S.; Agapitos, A.; Ahmad, A.; Ahmed, A.; Ahmed, A.; Ahmed, W.; Amarjeet, S.; Asghar, I.; Aspell, P.; et al.
Abstract: A temperature monitoring system based on fibre Bragg grating (FBG) fibre optic sensors has been developed for the gas electron multiplier (GEM) chambers of the Compact Muon Solenoid (CMS) detector. The monitoring system was tested in prototype chambers undergoing a general test of the various technological solutions adopted for their construction. The test lasted about two years and was conducted with the chambers being installed in the CMS detector and operated during regular experimental running. In this paper, we present test results that address the choice of materials and procedures for the production and installation of the FBG temperature monitoring system in the final GEM chambers.